The clock is ticking! Executive temporal depth, industry velocity, and competitive aggressiveness - Nadkarni, Sucheta; Chen, Tianxu; Chen, Jianhong (Strategic Management Journal, 2016)
We examine how the interplay between executive temporal depth (time horizons that executives consider when contemplating past and future events) and industry velocity (the rate at which new opportunities emerge and disappear in an industry) shapes competitive aggressiveness (a firm's propensity to challenge rivals directly and intensely in order to maintain or improve its market position) and firm performance. Based on panel data (from 1995 to 2000) from 258 firms in 23 industries, we found that executive temporal depth exhibited different patterns of relationships with competitive aggressiveness in low‐ and high‐velocity industries. Moreover, competitive aggressiveness had a positive main effect on firm performance, but this effect was stronger in high‐velocity industries than in low‐velocity industries . Copyright © 2015 John Wiley & Sons, Ltd.